Kualitas Pelayanan dan Bauran Promosi Mempengaruhi Keputusan Pembelian Konsumen di Ak Phone Jambi Kota Jambi - Tarmizi, Ahmad; Asmas, Denny; Yola, Natasya; Adisetiawan, R. (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the influence of the promotion mix and service quality on purchasing decisions at AK Phone Jambi City. The data collection methods used were interviews, observation, and questionnaires in the form of questionnaires. The sample in this study consisted of 99 respondents. The analytical tool used in this research is multiple regression analysis. The results of this research reveal that simultaneously and partially there is a significant and positive influence between the promotional mix variables and service quality on purchasing decisions at the Ak Phone Shop, Jambi City.